A novel generalized photo-thermoelasticity model for hydro-poroelastic semiconductor medium - Merfat H. Raddadi; Munirah Aali Alotaibi; Alaa A. El-Bary; Khaled Lotfy (AIP Advances)
This study applies the generalized photo-thermoelasticity theory to investigate thermo-hydro-mechanical interactions in a poroelastic half-space elastic semiconductor material with variable properties. The model represents a novel approach, treating the material as a uniform, fully saturated, poroelastic semiconductor half-space in alignment with the principles of dynamic poroelasticity within generalized photo-thermoelasticity. We initially applied time-harmonic loads, encompassing normal or thermal loads and plasma electron distributions to this medium. The study then explores the differences between coupled thermo-hydro-mechanical dynamic models and thermo-elastic dynamic models. We employed two-dimensional normal mode analysis to solve the resulting non-dimensional coupled equations. Subsequently, we examined the impact of non-dimensional displacement, excess pore water pressure, mechanical stress, carrier concentration (density), and temperature distribution on the poroelastic half-space medium. We then visually represented these effects.